ANALYSIS OF STUDENT MATHEMATICS REPRESENTATION IN SOLVING MINIMUM COMPETENCY ASSESSMENT PROBLEMS BASED ON MATHEMATICS ABILITY - Khofifah Irma Fela Sisyanti; Moh Zayyadi; Ukhti Raudhatul Jannah; Sri Irawati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Representation is a form of interpretation of students' thoughts on a problem. One of the evaluation tools organized by the Ministry of Education and Culture is the Minimum Competency Assessment which is used to measure students' cognitive abilities where the aspects measured are reading literacy skills and numeracy literacy. From the results of observations, students are still not ready to face the minimum competency assessment and are still unable to answer mathematical problems mathematically. It is necessary to know how the students' mathematical representation abilities in solving the minimum competency assessment problems. This research is qualitative descriptive research. with data collection techniques in the form of tests and interviews. The subjects in this study were three students with different mathematical abilities taken from class VIII-A of SMPN 1 Pamekasan. The results showed that students with high, medium, and low abilities gave representations of mathematical equations or expressions and representations of words or written texts, but only high and moderate abilities met all indicators. Only students with high math abilities involve precise visual representations, students with moderate math abilities do not correctly involve visual representations and students with low math abilities do not show visual representations